Endurance training, overtraining and baroreflex sensitivity in female athletes - Uusitalo, A. L.; Uusitalo, A. J.; Rusko, H. K. (1998)
We examined heavy training-induced changes in baroreflex sensitivity, plasma volume and resting heart rate and blood pressure variability in female endurance athletes. Nine athletes (experimental training group, ETG) increased intense training (70-90% VO2max) volume by 130% and low-intensity training (< 70% Vo2max) volume by 100% during 6-9 weeks, whereas the corresponding increases in six control athletes (CG) were 5% and 10% respectively. Maximal oxygen uptake (VO2max) in the ETG and CG did not change, but in five ETG athletes VO2max decreased from 53.0 +/- 2.2 (mean +/- SEM) (CI 46.8-59.2) ml kg-1 min-1 to 50.2 +/- 2.3 (43.8-56.6) ml kg-1 min-1 (P < 0.01), indicating overtraining. Baroreflex sensitivity (BRS) measured using the phenylephrine technique and blood pressure variability (BPV) did not change, but the low-frequency power of the R-R interval variability increased in the ETG (P < 0.05). The relative change in plasma volume was 7% in the ETG and 3% in the CG. The changes in BRS did not correlate with the changes in plasma volume, heart rate variability and BPV. We conclude that heavy endurance training and overtraining did not change baroreflex sensitivity or BPV but significantly increased the low-frequency power of the R-R interval variability during supine rest in female athletes as a marker of increased cardiac sympathetic modulation. Clin Physiol 1998 Nov;18(6):510-20